Evaluation of carrot varieties for morphological traits, yield attributes and nutritional profile in Bhaktapur, Nepal - Paudel, Pradeep; Subedi, Arjun (Journal of Agriculture and Natural Resources, 2023)
Carrot is an important root vegetable and commonly used as a snack, part of salads, cooked in curries and used in making pickles. A research was carried out to evaluate the performance of different carrot varieties for their morphological traits, yield attributing characters and nutritional parameters from Feb 2023 to June 2023 at Thimi Municipality-2, Bhaktapur. There were five carrot varieties such as Nepa Dream, Red Champion, Sigma, SK3, and New Kuroda. The experimental design was Randomized Complete Block Design with four replications. Results showed that there were significant differences in growth parameters, morphological characters, and nutrient composition. Nepa Dream showed the greatest root length (25.24 cm), weight (100.25 g), total yield (27.48 t/ha), βcarotenoid (12.34 mg/100 g), dry matter (12.35%) and TSS (11.25 ºBrix). New Kuroda had the maximum plant length (78.17 cm). The results of the current study showed that varieties differed significantly for morphological traits, yield attributes and other nutritional aspects. Nepa Dream was found to be the appropriate variety in terms of yield, TSS, β-carotene and dry matter content for growing at Thimi, Bhaktapur, Nepal. Among other varieties, SK3 seemed to be the promising for its overall traits and so it needs to be further tested over multiple seasons and locations.